Analisis Kata Kerja dan Frasa Kerja Bahasa Melayu Kokos di Pulau Home Australia (Jurnal Bahasa, 2010)
This article describes the forms of verb stem and verb phrase of the Malay language used by the Malays in the Cocos Islands, Australia, especially on Home Island, located in the Indian Ocean, outside the Malay world. The study is based on the framework introduced by Emeritus Professor Dato' Dr. Asmah Haji Omar (2008). The study focuses on the usage of verbs and verb phrases in everyday communication among the island's Malay community. Interviews with open-ended questions were constructed to elicit responses from the informants and observations made. Based on the data collected, the verbs and verb phrases found in Cocos Malay sentence-structure are complex verbs and compound verbs which include single-word verbs, derivations of verbs, transitive and intransitive verbs and auxiliary verbs. The results show that the Cocos Malay uses verbs as a grammatical system which can be divided into certain subsystems which are important in relation to context and meaning.Keywords: Cocos Malay, verbs stem, verb phrase, grammatical system